Empowerment of the Community Through the Utilization of Yards in Narrow Areas of My Village, Gajah District, Darul Imarah Sub-district, Aceh Besar Regency - Mujiburrahmad, Mujiburrahmad; Kesumawati, Elly; Saputra, Kurnia (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This study explores the underutilization of backyard land in Gajah Village for horticultural cultivation, focusing on vertical farming techniques. It addresses knowledge gaps in optimizing backyard space and producing organic fertilizers and pesticides from household waste. Method: The research adopts a participatory approach involving coordination, socialization, surveys, interviews, and practical training sessions. Counselling on vertical farming, Liquid Organic Fertilizer (LOF) production and botanical pesticides is provided. Practical Applications: The study's findings empower the community to enhance food security, income, and environmental sustainability through sustainable vegetable production. It informs policy interventions for promoting grassroots-level sustainable agriculture. Conclusion: This research emphasizes community empowerment and skill-building to address agricultural challenges. Optimizing backyard land and promoting organic farming practices contributes to resilient and sustainable agriculture, leveraging local resources for improved livelihoods.